A practical synthesis of fluoroquinolone antibiotic moxifloxacin - Thanh, Le Nguyen; Giap, Tran Huu; Tung, To Hai; Dung, Nguyen Anh; My Hue, Van Thi; Hue, Cao Thi; Minh Hang, Nguyen Thi; Hung, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
The fluoroquinoloneantibiotic has been used in clinical practice since the 1980s, primarily for the treatment infections caused by Gram-negative bacteria. Moxifloxacin, a fourth-generation fluoroquinolone antibiotic developed by pharmaceutical company Bayer AG, exhibit broad spectrum of activity against Gram-negative, Gram-positive bacteria as well as anaerobia. Moxifloxacin is used for community-acquired respiratory tract infections, sinusitis, acute exacerbations of chronic bronchitis and pneumonia, and skin structure infections. We have described the synthesis of moxifloxacin using difluoroboron complex. In this paper, a practical synthesis of moxifloxacin using acetoxyboronate complexwas reported.